Development of Complaint Monitoring Method for Levonorgestrel Intrauterine System Products - Aunio, Riitta (My University, 2023)
The central purpose of quality and risk management in pharmaceutical industry is to protect the safety of the population using the medicinal products. Complaint management is essential part of quality and risk management since complaints are a source of external feedback that provide important information regarding the risks and product vulnerabilities. Levonorgestrel Intrauterine system products offer a long-term reversible contraception. The duration of use for the LNG-IUS products is up to 3-8 years depending on the product and the indication. Thus, complaints are received several years after the production is completed. In addition, variation in complaint reporting, such as reimbursement policies or overall country specific quality infrastructure may have an impact on the complaint data. The goal of this research is to develop a control chart to monitor the complaint rate per bulk batch. To support control chart development complaint data is organized on postproduction timeline to identify timepoints for the complaint rate monitoring. The relationship of confirmed complaints and complaint rate is investigated with scatterplots to evaluate the impact of the other factors. Control charts for complaint rate per bulk batch were developed based on 3-parameter Weibull distribution, however, implementation of these control limits into actual monitoring requires further optimization and validation. Scatterplots suggested that in-control situation high variation in complaint rate between the bulk batches is not attributed to quality related factors.
Keywords: complaint management, LNG-IUS, control chart